The Fabrication of Docetaxel-Containing Emulsion for Drug Release Kinetics and Lipid Peroxidation - Yifang Wu; Mengmeng Wang; Yufan Li; Hongmei Xia; Yongfeng Cheng; Chang Liu; Ying Xia; Yu Wang; Yan Yue; Xiaoman Cheng; Zili Xie (MDPI AG, 2022)
Docetaxel (DTX)-based formulation development is still confronted with significant challenges, due to its refractory solubility and side effects on normal tissues. Inspired by the application of the transdermal drug delivery model to topical treatment, we developed a biocompatible and slow-release DTX-containing emulsion via self-assembly prepared by a high-speed electric stirring method and optimized the formulation. The results of accelerated the emulsion stability experiment showed that the emulsion prepared at 10,000 rpm/min had a stability of 89.15 ± 2.05%. The ADME, skin irritation, skin toxicity and molecular interaction between DTX and excipients were predicted via Discovery Studio 2016 software. In addition, DTX addition in oil or water phases of the emulsion showed different release rates in vitro and ex vivo. The DTX release ex vivo of the DTX/O-containing emulsion and the DTX/W-containing emulsion were 45.07 ± 5.41% and 96.48 ± 4.54%, respectively. In vitro antioxidant assays and anti-lipid peroxidation models revealed the antioxidant potential of DTX. However, DTX-containing emulsions could maintain and even enhance the antioxidant effect, both scavenging free radicals in vitro and inhibiting the process of lipid peroxidation.